Ifosfamide, paclitaxel and cisplatin first-line chemotherapy in advanced, suboptimally debulked epithelial ovarian cancer - Papadimitriou, C.A.; Kouroussis, C.; Moulopoulos, L.A.; Vlahos, G.; Rodolakis, A.; Kiamouris, C.; Diakomanolis, E.; Gika, D.; Michalas, S.; Dimopoulos, M.A. (Cancer, 2001)
BACKGROUND. The combination of paclitaxel with a platinum analogue is the preferred chemotherapy regimen in the treatment of advanced epithelial ovarian carcinoma. The alkylating agent ifosfamide has shown activity in refractory or recurrent ovarian cancer. We conducted a Phase II study with the combination of ifosfamide, paclitaxel, and cisplatin for the treatment of newly diagnosed patients with advanced, suboptimally debulked ovarian carcinoma. METHODS. Thirty-five consecutive patients with advanced ovarian carcinoma (International Federation of Gynecology and Obstetrics [FIGO] Stage III or IV) and residual disease larger than 2 cm after staging laparotomy and cytoreductive surgery were treated with paclitaxel, 175 mg/m2, as a 3-hour intravenous infusion on Day 1, cisplatin 75 mg/m2 intravenously over 2 hours on Day 2, and ifosfamide 1500 mg/m2 intravenously over 1 hour on Days 1-3 (with sodium 2-mercaptoethane sulfonate [MESNA] uroprotection). Courses were administered every 3 weeks on an outpatient basis. Granulocyte-colony stimulating factor was given at a dose of 5 μg/kg/day on Days 7-11. RESULTS. Among 26 patients with measurable disease, 22 (85%) achieved an objective response including 15 complete and 7 partial responses. With a minimum follow-up of 46 months, the median overall survival was 52.8 months (range, 5.3-56.6+ mos), whereas the median time to progression for all patients was 22.2 months. The median remission duration for women with measurable disease who responded to treatment was 12.6 months. The treatment was tolerated relatively well without toxic deaths; the most common toxicity was Grade 3 or 4 neutropenia that occurred in 42% of patients. Significant peripheral neuropathy (Grade 2 or higher) developed in 35% of patients. CONCLUSION. The combination of ifosfamide, paclitaxel, and cisplatin is a well-tolerated outpatient regimen with significant activity in the treatment of newly diagnosed FIGO Stage III or IV epithelial ovarian carcinoma. Further evaluation is justified to clearly define the role of ifosfamide as an additional agent to the current platinum and paclitaxel regimens. © 2001 American Cancer Society.
Keywords: Advanced ovarian carcinoma; Cisplatin; First-line chemotherapy; Ifosfamide; Paclitaxel